ENTREPRENEURAL FIGURE OF MOUNT AGUNG TREKKING GUIDES - Mudana, I Gede; Sutama, I Ketut; Widhari, Cokorda Istri Sri (E-Journal of Cultural Studies; Volume 10, Number 3, August 2017, 2017)
Mount Agung with an altitude of 3,142 meters from sea level stood at the coordinates of 8020'27 "S 115030'12" E, circled along 105 kilometers (65 miles), and classified as a volcanic type monoconic strato. The highest mountain in Bali Province was located in Selat District, Karangasem Regency. It got a last major eruption in 1963 and since then began to be climbed by climbers/tourists. Because in 1970s and 1980s some climbers/tourists very often got lost and accidents to death, since the 1990s a number of the local community members took initiative to serve the climbers/tourists who want to explore the mountain known as holy and sacred one. This study was conducted in order to understand and describe the pioneering aspects of entrepreneurial figure of the related trekking guides. It was a qualitative study with a qualitative data analysis. The results of this study showed that because Mount Agung was not an ordinary mountain but full of myths and stories that were supernatural, so the entrepreneurial practices of the Selat Village community appeared not only to serve the climbers/trekkers as usual but also to preserve the environment and ensure their safety as there were so many taboos in the climbing/trekking. All these facts can be seen from the depiction of the stories and experiences of the local climbing/trekking guides who had been doing their work for years. As entrepreneurs, they looked for income but, above all, environmental sustainability and the spirituality of the mountain werw not neglected.